(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article highlights that Alexander created the public opinion he needed through diplomatic means; used the struggle of various party groups to achieve his goal; separated the forces and opposition that rebelled against him. He also demonstrated his diplomatic skill in political and religious demonstrations; in diplomatic games both with one’s own army and with the conquered population; in pursuing a subtle policy of relations with defeated countries and peoples.